The Development of Interactive Learning Media Based on Articulate Storyline 3 on Thermochemistry to Enhance Student's Conceptual Understanding - Faiza Ulayya Warfi; Eko Budi Susatyo; Sri Haryani (Universitas Negeri Semarang, 2026)
This study aimed to develop an interactive learning medium based on Articulate Storyline 3 for thermochemistry material, as well as to determine its feasibility, effectiveness, and user response. This research was motivated by the low conceptual understanding of students regarding the abstract nature of thermochemistry and the limited use of media, which was confined to textbooks and PowerPoint at SMA Teuku Umar Semarang. The research method used was Research and Development (R&D) with the 4D model (Define, Design, Development, Disseminate ). The research subjects consisted of 25 grade XII science students for a small-scale trial and 33 grade XI science students for a large-scale trial. Data were collected through interviews, expert validation questionnaires, response questionnaires, and conceptual understanding tests (pre-test and post-test). The results showed that the learning medium was declared